Evaluation of the effectiveness of osteopathic treatment on the mother-newborn dyad in the event of painful breastfeeding in a maternity hospital despite the application of all usual aids: randomized interventional trial in two parallel arms without blinding - Elleau, Christophe; Missmahl, Corine; Belcadi, Wafae; Aurillac-Lavignolle, Valérie; Sentilhes, Loic (Frontiers in Nutrition, 2025)
AimPain during breastfeeding is the first reason for stopping breastfeeding. When conventional aids are ineffective, osteopathic manipulative treatment (OMT) may be an option to reduce pain and improve the quality and duration of breastfeeding. The objective is to compare conventional aids (untreated group) versus conventional aids combined with OMT (tactile listening) for both the baby and the mother (treated group). The primary outcome is the breastfeeding rate 1 month after birth. Patients were included in the maternity ward of the University Hospital Center of Bordeaux from March 23, 2022, to April 23, 2024. The inclusion criteria was breastfeeding pain greater than 7 (scale from 0 to 10) in one or both breasts. The mother had to be aged 18 years or older, with a singleton newborn, born after 37 weeks of gestation, weighing at least 2,500 g and included after 36 h of life.Results23 mother-infant dyads were included, 13 in the treated group and 10 in the untreated group. The average pain score for the most painful breast was 9/10 in both groups. One month after birth, breastfeeding was ongoing in 11 dyads in the treated group and 3 in the untreated group (p = 0.01), exclusive breastfeeding was ongoing in 8 dyads in the treated group and 1 in the untreated group (p = 0.03). Three dyads left the study after stopping breastfeeding.DiscussionOur study was prematurely terminated due to difficulties in patient recruitment caused by breastfeeding cessation or parental refusal of randomization. OMT appears useful in cases of highly painful breastfeeding, facilitating the effectiveness of professionals providing conventional support. Another study conducted in France did not show a beneficial effect: only the baby was treated with the mother separated behind a screen, the inclusion criteria was composite (IBFAT), OMT was not clearly defined as soft touch. Treating the baby without the mother is not relevant, particularly when the objective is to improve breastfeeding, which requires perfect synchrony between mother and infant. We consider it crucial to conduct further studies, enrolling participants earlier and targeting an audience without prior knowledge or biases regarding osteopathy.Clinical trial registrationhttp://www.clinicaltrials.gov/, identifier AMATOSTEO NCT 05185323.